Effects of biochar and slurry application as well as drying and rewetting on soil macro‐aggregate formation in agricultural silty loam soils. (17th December 2018) - Grunwald, D.; Kaiser, M.; Piepho, H.‐P.; Koch, H.‐J.; Rauber, R.; Ludwig, B.
Abstract: Biochar application in combination with slurry might be an option to increase aggregate formation and organic carbon (OC) sequestration in agricultural soil. However, to assess the value of these management options for improving soil structure more precisely, naturally occurring effects of changing moisture on soil aggregation and feedbacks on organic matter (OM) decomposition need to be addressed. Therefore, we aimed to quantify the effects of biochar or slurry application on the amount of OC associated with macro‐aggregates and OM decomposition under different moisture conditions. Four silty loam sites in Germany were sampled, and the soil macro‐aggregates were crushed. We added biochar (53–250 μ m) and slurry individually and in combination at two rates before incubating the samples under changing moisture conditions for 60 days. As well as monitoring CO2 fluxes, samples were analyzed for microbial biomass carbon, macro‐aggregate yields and macro‐aggregate‐associated OC. Biochar application decreased macro‐aggregate yields by 50–70%. However, the macro‐aggregate‐associated OC of treatments with biochar was similar to or greater than in treatments without, indicating biochar incorporation into these fractions. This was especially pronounced for biochar treatments with large volumes of slurry. Thus, slurry seems to promote the formation of biochar–mineral interactions. Drying and rewetting decreased macro‐aggregate yields and associated OC, being most pronounced for samples with biochar and slurry. In contrast to slurry, biochar typically did not increase macro‐aggregate formation. However, the combination with slurry could further enhance the suitability of biochar for carbon sequestration, although this might be less pronounced in soils experiencing frequent drying‐wetting cycles.